2008
DOI: 10.2133/dmpk.23.347
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Species Similarity of OATP Transporters Responsible for Hepatic Uptake of β-Lactam Antibiotics

Abstract: The present study was designed to identify the organic anion transporting polypeptide (OATP) molecule(s) responsible for the uptake of beta-lactam antibiotics in human liver, using cryopreserved hepatocytes, as well as Xenopus oocytes and cultured cells expressing human OATPs. Nafcillin uptake by human hepatocytes was saturable with a Km of 533 microM. In vitro uptake studies revealed that OATP1B3 and OATP1B1 transported nafcillin with Km values of 74 microM and 11 mM, respectively. Analysis by the relative ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 24 publications
0
36
2
Order By: Relevance
“…Other substrates (rifampicin and penicillin for OATP1B1; rifampicin, penicillin, cefmetazole, and cefoperazone for OATP1B3) were consistent with previous reports. 21,25,26) The report by Nakakariya et al, 26) which demonstrated that cefoperazone is transported by OATP1B1 and that cefazolin is transported by both OATP1B1 and OATP1B3, was inconsistent with our results. We did not perform the uptake study if the transporter-mediated uptake did not decrease to 50% of the control uptake at the maximum inhibitory concentration.…”
Section: Discussioncontrasting
confidence: 99%
“…Other substrates (rifampicin and penicillin for OATP1B1; rifampicin, penicillin, cefmetazole, and cefoperazone for OATP1B3) were consistent with previous reports. 21,25,26) The report by Nakakariya et al, 26) which demonstrated that cefoperazone is transported by OATP1B1 and that cefazolin is transported by both OATP1B1 and OATP1B3, was inconsistent with our results. We did not perform the uptake study if the transporter-mediated uptake did not decrease to 50% of the control uptake at the maximum inhibitory concentration.…”
Section: Discussioncontrasting
confidence: 99%
“…In such cases, there might be potential competition between Ba and non-steroidal antiinflammatory drugs (NSAIDS) such as acetaminophen, ibuprofen or naproxen, etc. on phase II metabolic enzymes (26) or potential competition between Ba conjugates and NSAIDS conjugates on MRPs (27,28), as well as potential competition between Ba conjugates and antibiotics such as beta-lactam antibiotics on OATPs (29). All of those interactions may lead to the alteration of the clinical pharmacokinetic profiles of Western drug and should be taken into consideration in designing a therapeutic regimen.…”
Section: −1mentioning
confidence: 99%
“…22) In general, uptake reaction was initiated by placing the cells in transport buffer (136.7 mM NaCl, 5. Transport Study Using Xenopus laevis Oocytes Complementary RNAs (cRNAs) of human OAT2 were prepared using a mMESSAGE mMACHINE kit according to manufacturer's instruction (Ambion, Austin TX, U.S.A.).…”
Section: Chemicalsmentioning
confidence: 99%